Self-efficacy in the relationship between illness perception and predicted psychotropic treatment compliance amongst adolescent inpatients - Franken, Anneke Louise (University of the Free State, 2019)
Mental illnesses are increasingly being diagnosed among adolescents, and as a result there is an increase in the prescription of psychotropic medication. Non-compliance with psychotropic treatment appears to be a growing problem amongst adolescent mental health care users. Treatment is frequently initiated during hospitalisation periods, which poses the risk that the in-patient may become non-compliant once responsibility for taking treatment is transferred to them on discharge. Though there are a multitude of factors that contribute to treatment compliance amongst adolescents, it appears that self-efficacy, participation in the decision-making process concerning the treatment pathway, and the ways in which mental illness is perceived are significant determinants of treatment compliance. The aim of this study was to investigate which factors influence psychotropic treatment compliance among South African adolescent inpatients admitted to a psychiatric facility. A quantitative, non-experimental, cross-sectional, survey-type research design was employed. Approximately 170 participants were selected through a nonprobability convenience sampling method. Data was gathered by using self-report measures, namely the Drug Attitude Inventory, the Brief Illness Perception Questionnaire, and the Decision Self-Efficacy Scale. The correlation between the variables was calculated through a Pearson Product correlation coefficient, and a hierarchical regression analysis was utilised to determine the role of self-efficacy in the relationship between illness perception and treatment compliance. The results indicated that there is no significant relationship between treatment compliance and illness perception, but there is a significant relationship between illness perception and self-efficacy. Self-efficacy was identified as a moderator between illness perception and treatment compliance of male adolescent inpatients. The findings of the study and the gender difference which surfaced may contribute towards a better understanding of the intricate processes related to treatment compliance in adolescents and help direct intervention aimed at promoting treatment compliance.
Dissertation (M.Soc.Sc. (Clinical Psychology))--University of the Free State, 2019
Keywords: Treatment compliance; Psychotropic treatment; Illness perception; Self-efficacy; Adolescents